Innovation of marketing supply chain management model based on SICAS modeling - Mao, Rui; Liu, Youwei; Yang, Yida (Sciendo, 2024)
The marketing service system is not perfect enough to highlight the competitive advantages of enterprises, and improving the marketing supply chain management mode is an inevitable trend under the change of the market economic environment. The marketing supply chain management model proposed in this paper is based on the SICAS model to respond quickly to market and customer demand. A collaborative optimization model of the supply chain based on virtual inventory management is constructed to ensure the normal operation of the whole supply chain by deploying flexible inventory in the hands of customers, and the constructed model is solved by using an evolutionary algorithm based on indexes and an optimal solution sorting method based on regret theory. The feasibility and scientificity of the proposed management model are verified by analyzing the effect of applying the management model to J and S e-commerce companies and analyzing consumer evaluation. The results show that from 2014 to 2022, the purchasing cost of J e-commerce enterprises decreased by 0.0307 as a proportion of operating income, the inventory turnover ratio increased by 0.0869, the marketing cost and logistics cost increased by 189 million yuan and 3,878 million yuan, respectively, and the supply chain cost was effectively managed. At the same time, the consumer evaluation score of the marketing supply chain management model based on SICAS model is 3.608±0.043 points; the user experience is good, to a certain extent, to enhance the competitive advantage of the enterprise.